Legal Review on Marriage Dispensation and Its Impact on Children's Right to Education - Kadir, Muthiara Afdillah; Talib, Mutia Cherawaty; Elfikri, Nurul Fazri (Estudiante Law Journal, 2025)
This research examines the impact of marriage dispensation on fulfilling children's right to education within the jurisdiction of the Suwawa Religious Court. Marriage dispensation grants permission for marriage for minors, which has significant implications for children's education, particularly the risk of early school dropout. Empirical data reveals a high number of marriage dispensation requests involving students, potentially hindering children's access to quality education and the optimal development of their potential. Furthermore, this study highlights broader social consequences, including reproductive health risks, psychological pressure, and vulnerability to domestic violence, all of which threaten the well-being of children. From a legal perspective, although the regulation of Law No. 16 of 2019 and PERMA No. 5 of 2019 provides strict guidelines in the dispensation process, practical implementation still faces challenges in ensuring children's rights are heard and their best interests are prioritized. This situation calls for serious attention from the judiciary and relevant stakeholders. The study concludes the need for strengthening judges' capacity through training, legal assistance, and community education to change the social norms still influencing child marriage practices. A comprehensive policy recommendation is aimed at strengthening regulations, improving inter-agency synergy, and ensuring effective supervision to maximize the protection of children's educational rights. This study is expected to contribute to the development of child protection policies and enhance Indonesia's human resources in the future.